Preparation of yeast Saccharomyces cerevisiae biomass enriched with ergosterol and cyanocobalamin - Fatkullin Rinat I.; Kalinina Irina V.; Goryacheva Sofya A.; Stepanova Darya S.; Erykalova Vasilina D. (BIO Web of Conferences)
Chemical synthesis of vitamins B12 and D2, important nutrients for living organisms, is difficult due to the asymmetric structure of the molecules of these vitamins. For this reason, the prospects for the development of biotechnological approaches for the synthesis of cyanocobalamin and vitamin D2, which forms the basis of this work, are enormous. The use of yeast Saccharomyces cerevisiae was proposed as a producer. These microorganisms are the most well-studied, widely used in the food industry, and are safe, easy enough to cultivate. The study considers the possibility of using yeast biomass as a feed or food additive - a source of cyanocobalamin and ergosterol (precursor of vitamin D2). The possibility of using alcohol production waste - rye bard - as a nutrient medium is being studied. Cultivation and evaluation of the content of the desired metabolites were carried out in comparison with the control nutrient medium YEPD. The yeast biomass growth after 18 hours of cultivation and the content of ergosterol and cyanocobalamin in the biomass at the beginning and the end of cultivation were evaluated. The results showed the viability of the proposed approach for culturing Saccharomyces cerevisiae yeast on alcoholic bard. At the same time, the commercialization of technology requires the search for effective ways to intensify the synthesis of ergosterol and cyanocobalamin by yeast cells.